2013
DOI: 10.1002/cncr.28407
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for preoperative prediction of prognosis in patients with oral cavity squamous cell carcinoma

Abstract: BACKGROUND: This study sought to develop prognostic tools that will accurately predict overall and cancer-related mortality and risk of recurrence in individual patients with oral cancer based on host and tumor characteristics. These tools would take into account numerous prognosticators beyond those covered by the traditional TNM (tumor-node-metastasis) staging system. METHODS: Demographic, host, and tumor characteristics of 1617 patients with cancer of the oral cavity, who were treated primarily with surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
115
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 26 publications
6
115
0
1
Order By: Relevance
“…11,19,[22][23][24][25][26][27] For head and neck cancer, competing risk nomograms for oral cavity squamous cell carcinoma and salivary glands cancer have been recently developed. 28,29 However, both study cohorts were collected from a single institution, and models may not be relevant to risk prediction in general populations. Population-based competing risk nomograms for HNSCC are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…11,19,[22][23][24][25][26][27] For head and neck cancer, competing risk nomograms for oral cavity squamous cell carcinoma and salivary glands cancer have been recently developed. 28,29 However, both study cohorts were collected from a single institution, and models may not be relevant to risk prediction in general populations. Population-based competing risk nomograms for HNSCC are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms have been used in several cancers as adjuncts in prognostic determination 8,4749 . They can be tools to determine patient prognosis in addition to TNM classification, the current gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis for overall survival (OS) and risk of recurrence depends on both tumor-specific factors such as tumor size, nodal status, distant metastasis, extranodal extension (ENE) and bone invasion as well as patient-specific factors such as age, smoking, race, comorbidities and sex 2–6 . Although the TNM classification is important for predicting clinical outcomes and to serve as a guide for ablative and reconstructive treatment, OS vary greatly, even in patients at the same disease stage 7,8 . Recent reports have suggested that patient prognosis is associated with certain molecular biomarkers involved in angiogenesis, cell mutation, proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Differences between calculators are determined by what factors are included in the equations, how they are included, as well as the quality and relevance of the datasets from which they were derived. Comorbidities, which are an important factor in determining overall survival (24), are included in three of the calculators, and MSK was the only calculator to use the Washington University Head and Neck Comorbidity Index (WUHNCI) (16, 24). …”
Section: Discussionmentioning
confidence: 99%